Optimasi Konsentrasi Fe(II) pada Metode Wet Peroxide Oxidation (WPO) untuk Identifikasi Mikroplastik Polypropylene (PP) - Mainita, Yosi Putri; Dewata, Indang (Lembaga Yasin AlSys, 2024)
One of the global problem is plastic waste, if not handled properly it will cause waterpollution. Plastic will degrade into samall pasrticles called microplastic. Polyperopylene plastic will be cut very small size and soaked in water and left in an open room for one month, so that the microplastic degrade naturally and become contaminated by organic impurities. The method used is Wet Peroxide Oxidation (WPO) which was adapted from the National Oceanic and atsmospheric (NOAA). Optimization was carried out the concentration of the Fe(II) catalyst with variations (0.025, 0.05, 0.075, 0.1, 0.125) M. The research result showed that the optimum condition for the Fe(II) consentration was 0.1 M as evidenced by the microplastic mass obtained. Characterization tests were carried out using a stereo microscope, and microplastics were found in the form of fragments and filament.